Comparative analysis of types of combined anesthesia for laparoscopic cholecystectomy - O P. Melnyk (Ендоваскулярна нейрорентгенохірургія, 2017)
Objective – to evaluate through comparative analysis the effectiveness of different types of combined anesthesia during laparoscopic cholecystectomy performed under carboxyperitoneum conditions.